Discontinuation of immune checkpoint inhibitors for reasons other than disease progression and the impact on relapse and survival of advanced melanoma patients. A systematic review and meta-analysis - Lallas, Konstantinos; Chatziioannou, Eftychia; Durak, Derya; Frey, Georg; Serna-Higuita, Lina Maria; Rasch, Marie-Lena; Kyrgidis, Athanassios; Timotheadou, Eleni; Apalla, Zoe; Leiter, Ulrike; Flatz, Lukas; Lallas, Aimilios; et al. (Frontiers in Immunology, 2025)
BackgroundDespite durable responses achieved with Immune Checkpoint Inhibitors (ICIs), data about optimal duration of treatment, especially in the context of adverse events, remain scarce.ObjectiveTo systematically review the evidence concerning the impact of treatment discontinuation with ICIs for reasons other than progressive disease (PD) on relapse rates and survival of melanoma patients.MethodsA systematic literature search was conducted in three electronic databases until July 2024. Studies referring to melanoma patients who ceased ICIs electively (i.e. due to complete response (CR), protocol completion or patient/physician’s wish) or due to treatment-limiting toxicities (TLTs) were selected. Relapse rates (RRs) post cessation, time to PD, rechallenge and disease control rate (DCR) after 2nd course were the main outcomes. Random-effects models were preferred, and subgroup and sensitivity analyses were conducted to investigate possible sources of heterogeneity.Results38 and 35 studies were included in qualitative and quantitative synthesis, respectively. From 2542 patients discontinued treatment with ICIs electively or due to TLTs, 495 experienced progression [number of studies (n)=34, RR 20.9%, 95%CI 17.1 – 24.7%, I2 85%) and higher rates were detected in patients with TLTs compared to elective discontinuation. Mean time to PD was 14.26 months (n=18, mean time 14.26, 95%CI 11.54 – 16.98, I2 93%) and was numerically higher in patients who ceased for CR compared to patients with TLTs. Treatment duration before cessation was not associated with risk and time to relapse, while mucosal melanomas and non-CR as BOR during treatment led to increased risk for relapse and shorter time to PD compared to other histologic subtypes or CR. Rechallenge with ICI resulted in 57.3% DCR and 28.6% pooled CR rates (n=22, CR rate 28.6%, 95%CI 17.1 – 40.2, I2 68%). Heterogeneity among studies was high, but subgroup analysis based on type of ICI used (anti-CTL4 and anti-PD1 inhibitor or anti-PD1 monotherapy) and type of study (RCTs or observational studies), along with sensitivity analyses did not reveal significant alterations in results.ConclusionDiscontinuation of ICIs in patients without progression is possible. Outcomes to rechallenge with ICIs may differ depending on the reason for discontinuation, but remains a considerable option.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024547792.